Anatomical and histochemical analysis of Hoya pentaphlebia MERR. flower: insights into structure and chemical composition - Syazwani Basir,; Noraini Talip,; Hamidun Bunawan,; Ruzi Abdul Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Hoya R.Br. is an epiphytic plant known as an exotic ornamental plant with distinctive, unique, and fragrant flowers. Investigating its floral structure is crucial for understanding how these structures may contribute to the production and storage of secondary metabolites emitted by Hoya. This study aimed to identify the type and position of floral glands in Hoya pentaphlebia. The investigations began by identifying the type and position of the floral glands, utilizing light microscopy, electron microscopy, and histochemical staining techniques. Secondary nectaries (sn) were discovered in the corona lobe, while conical-shaped glandular trichomes (unicellular) (ct) were at the adaxial epidermis of the corolla. The secretory activity of proteins, lipids, polysaccharides, and starch grains was found in sn, whereas ct detected only lipids and proteins. Subsequent studies to identify the secondary metabolite profiles characterizing aroma emitted from H. pentaphlebia flowers using gas chromatography-mass spectrometry (GC-MS) showed 26 compounds were identified, with the methyl salicylate (MeSA) compounds being the most abundant. In conclusion, this study successfully identified the floral glands and secondary metabolites present as aromas in the species studied. Sn and ct were discovered to be present for the first time in H. pentaphlebia, providing new information into the Hoya’s floral structures. The presence of floral glands indicates the existence of secondary aromatic metabolites that play a role in the interaction between plants and numerous environmental elements.